Role of Multi-parameter-based Cardiac Magnetic Resonance in the Evaluation of Patients with Coronary Heart Disease Combined with Heart Failure - Yu, Ying; Liao, Bihong; Zhang, Jingjing; Zou, Jin; Deng, Jia; Liu, Jiaqi; Wang, Gang; Li, Yueyan; Qian, Fengcui; Huang, Hong; Wang, Qiuyu; Tian, Jinwei; et al. (Current Medical Imaging, 2024)
BackgroundCoronary Heart Disease (CHD) is one of the most common types of cardiovascular disease, and Heart Failure (HF) is an important factor in its progression. We aimed to evaluate the diagnostic value and predictors of multiparametric Cardiac Magnetic Resonance (CMR) in CHD patients with HF.MethodsThe study retrospectively included 145 CHD patients who were classified into CHD (HF+) (n = 91) and CHD (HF–) (n = 54) groups according to whether HF occurred. CMR assessed LV function, myocardial strain and T1 mapping. Multivariate linear regression analyses were performed to identify predictors of LV dysfunction, myocardial fibrosis, and LV remodeling.ResultsCHD (HF+) group had impaired strain, with increased native T1, ECV, and LVM index. The impaired strain was associated with LVM index (p < 0.05), where native T1 and ECV were affected by log-transformed amino-terminal pro-B-type natriuretic peptide (NT-proBNP) levels. ROC analysis showed the combination of global circumferential strain (GCS), native T1, and LVM had a higher diagnostic value for the occurrence of HF in CHD patients.Meanwhile, log-transformed NT-proBNP was an independent determinant of impaired strain, increased LVM index, native T1 and ECV.ConclusionHF has harmful effects on LV systolic function in patients with CHD. In CHD (HF+) group, LV dysfunction is strongly correlated with the degree of LV remodeling and myocardial fibrosis. The combination of the three is more valuable in diagnosing HF than conventional indicators.
Keywords: Left ventricular remodeling